2021
DOI: 10.1038/s41598-021-01854-7
|View full text |Cite
|
Sign up to set email alerts
|

Improved spatio-temporal measurements of visually evoked fields using optically-pumped magnetometers

Abstract: Recent developments in performance and practicality of optically-pumped magnetometers (OPMs) have enabled new capabilities in non-invasive brain function mapping through magnetoencephalography. In particular, the lack of cryogenic operating conditions allows for more flexible placement of sensor heads closer to the brain, leading to improved spatial resolution and source localisation capabilities. Through recording visually evoked brain fields (VEFs), we demonstrate that the closer sensor proximity can be expl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Magnetomyography [155,171], MEG [5,89,129,130,136,[172][173][174][175][176], MCG and fMCG [21,22,98,128,174,177], magnetic-field imaging [178] Magnetic biomarkers [132,[179][180][181][182] Biomagnetism of plants [183,184] and livestock [185] Zero-/low-field NMR [133,134,149,[186][187][188][189][190][191][192][193]] Geophysics [91,194] Aerospace [108,195] Laser guide stars [196]…”
Section: Biomedicalmentioning
confidence: 99%
“…Magnetomyography [155,171], MEG [5,89,129,130,136,[172][173][174][175][176], MCG and fMCG [21,22,98,128,174,177], magnetic-field imaging [178] Magnetic biomarkers [132,[179][180][181][182] Biomagnetism of plants [183,184] and livestock [185] Zero-/low-field NMR [133,134,149,[186][187][188][189][190][191][192][193]] Geophysics [91,194] Aerospace [108,195] Laser guide stars [196]…”
Section: Biomedicalmentioning
confidence: 99%
“…MEG is a nerve imaging technology that can measure the magnetic field near the head. [ 13,46,47 ] Recent studies have shown that MEG can be used to evaluate neurological diseases such as Alzheimer's disease, [ 48 ] Parkinson´s disease, [ 49 ] and autism spectrum dysfunction. [ 50 ] Despite their considerable potential, existing MEGs also exhibit significant limitations.…”
Section: Brain–computer Interfacesmentioning
confidence: 99%
“…Besides, the use of MEG is confined to magnetically shielded rooms (MSR), [ 13 ] because it needs MSR to suppress the magnetic noise from the environment, and this noise is typically many orders of magnitude higher than the neural magnetic field (fT to pT range). [ 51 ]…”
Section: Brain–computer Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomedical magnetomyography (MMG) [145,161], magnetoencephalography (MEG) [83,121,122,128,134,[162][163][164][165][166], (fetal) magnetocardiography (MCG and fMCG) [19,20,92,120,164,167], magnetic-field imaging (MFI) [168] magnetic biomarkers [124,[169][170][171][172] plant biomagnetism [173,174] Zero-/low-field NMR [125,126,139,[175][176][177][178][179]] Geophysics [85,180] Aerospace [102,181] Laser guide stars [182] Defense and industry underwater surveillance [135], electromagnetic induction imaging [183][184][185][186] Fundamental science search for new physics beyond particle standard model [38,76,…”
Section: Typical Applications Of Atomic Magnetometersmentioning
confidence: 99%